PENGARUH PENERAPAN PERATURAN PEMERINTAH NO 23 TAHUN 2018 TERHADAP EFISIENSI DAN EFEKTIVITAS PEMBAYARAN PAJAK PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA BANDA ACEH - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
The purpose of this study was to determine the effect of the Implementation of Government Regulation Number 23 of 2018 on the Efficiency and Effectiveness of Tax Payments at Banda Aceh Primary Tax Office. Samples were taken by purposive random sampling design technique. Data collection techniques by distributing questionnaires directly to respondents in the form of written questions. The analysis was carried out using a simple linear regression analysis technique with the SPSS 22.0 program. The results of the analysis show that the application of Government Regulation Number 23 of 2018 has a positive and significant effect on the acceptance of Income Tax Article 4 paragraph (2) at Banda Aceh Primary Tax Office. From the results of the significance test, it can be seen that the value of the variable influences the acceptance of Income Tax Article 4 paragraph (2) at Banda Aceh Primary Tax Office, which is 0,000 <0,05. From these results it can be concluded that Ho is rejected and Ha is accepted.